Major, trace and rare earth element (REE) geochemistry of different colored fluorites in the Bobrynets region, Ukraine - Sasmaz, Ahmet; Kryuchenko, Nataliya; Zhovinsky, Edward; Suyarko, Vasily; Konakci, Nevin; Akgul, Bunyamin (Elsevier Science Bv, 2018)
The Bobrynets fluorite mineralization in the exo-contact zone of Krivograd-Novoukrainian granite intrusion is found in the southern part of the Kirovograd-Cherkassy fault zone between the Novoukrainian anticlinoria and the Ingulo-Ingulets synclinoria. The fluorite mineralization appears as vein and disseminat, as well as in the form of a cement in the tectonic breccia among the metasomatically altered granites. Fluorite mineralization is observed for 5 km along this fault zone, down to a depth of 300 m with the thickness of the individual mineralized zones ranging from a few meters to 75 m, with average fluorite contents ranging from 1-2% to 28%. The estimated reserve of Bobrynets fluorites is approximately 1.56 million tonnes. Fluid inclusion data in the studied fluorites indicate that the study area has two types of fluorites: high temperature fluorites (240-280 degrees C) and low temperature fluorites (100-150 degrees C). The total rare earth element Sigma REE) contents of the fluorites range from 62.4 ppm to 527.9 ppm, with a mean of 218 ppm. The mean Sigma REE concentrations of different colored massive fluorites range from 80.2 ppm for yellow fluorites to 258 ppm for green fluorites, 97.4 ppm for violet fluorites and 526.5 ppm for granite samples. The mean Y concentrations of the studied fluorites are 86.2 ppm for violet fluorites, 104.5 ppm for yellow fluorites, 242.5 ppm for green fluorites and 39.9 ppm for granite samples. The chondrite-normalized REE patterns of the Bobrynets fluorites exhibit trends similar to each other and show a decrease from light REEs (LREE) to heavy REEs (HREEs). All fluorites in the study area have positive Ce anomalies between 1.06 and 1.16 (with mean of 1.12), negative Eu anomalies (with a range of 0.35 to 0.58; mean: 0.46), and positive Y anomalies between 1.38 and 2.67 (with mean of 2.12). The Y/Ho values change from 48.3 to 92.2 with mean of 71.1. The Tb/Ca and Tb/La ratios of the Bobrynets fluorites are between 0.00000249 and 0.0000404 and between 0.098 and 0.30, respectively, and these ratios also indicate a formation from fractionated ore-bearing fluids at an early stage of mineralization, mainly a hydrothermal and less pegmatitic stage. The (Tb/Yb)(n)-(La/Yb)(n) ratios are low because these fluorites are not LREE rich when compared to other fluorite deposits. The (La/Yb)(n)-(Eu/Eu*)(n) values also indicate low negative Eu anomalies and low LREE enrichments for the Bobrynets fluorites. The Sc/Eu vs Sr diagram and Sc vs Sigma REE diagram show that the Bobrynets fluorites have low Sr contents and high Sc/Eu values and that they cover the same areas as the Rift Deposits of New Mexico and the skarn fluorite deposits of Akdagmadeni. The (208)bp/(204)pb isotope values of fluorites vary between 53.5 and 62.6 and the Pb-206/Pb-204 isotope values of fluorites vary between 23.3 and 26.8. The (208)pb/(204)pb vs (206)pb/Pb-204 ratios indicate that fluorites originated from upper crust materials. All these findings indicate that REE contents of the Bobrynets fluorites have different physicochemical parameters such as decrease in temperature or increases in fO(2) and pH, high oxygen fugacity in the source of the hydrothermal fluids, and low Sr and high Sc values similar to rift and skarn deposits.
Keywords: Fluorite; REE geochemistry; Vein type; Bobrynets; Ukraine